KEMAMPUAN GEL EKSTRAK BIJI KOPI ROBUSTA (Coffea canephora) DALAM MENURUNKAN TRAP PADA TIKUS MODEL PERIODONTITIS YANG DIINDUKSI KOMBINASI LPS P. gingivalis DAN WIRE NITI - Rachmawati, Dessy; Setyaningsih, Sari; Herniyati; Rahmah, Tanzilal Azizir (Universitas Islam Negeri Alauddin Makassar, 2024)
Periodontitis is an inflammatory disease of the tooth supporting tissues caused by pathogenic microorganisms in dental plaque. P. gingivalis as the main etiology of periodontitis has a virulence factor in the form of lipopolysaccharide (LPS). The use of NiTi wires in initial orthodontic treatment can exacerbate periodontitis. Robusta coffee beans contain active compounds such as chlorogenic acid, caffeic acid, ferulic acid and caffeine as anti-inflammatories and antioxidants. This study aims to analyze the ability of robusta coffee bean extract gel to reduce TRAP in a rat model of periodontitis induced by the combination of LPS P. gingivalis and NiTi wire. The 28 male wistar rats were classified into 7 groups of normal (K), injected with LPS (P1), NiTi wire (P2), combination of LPS and NiTi wire (P3), injected with LPS and 500 mg/ml robusta coffee bean gel (P4), NiTi wire and 500 mg/ml robusta coffee bean gel (P5), combination of LPS and NiTi wire with 500 mg/ml robusta coffee bean gel (P6). The rats were decapitated, and then the tissue was stained with HE and IHC. The expression of TRAP was counted in the area around alveolar bone of the lower-left M1. Data were analyzed using SPSS software by going through several test, such as Saphiro-Wilk, Levene-Test, Kruskal-Wallis, and followed by Mann-Whitney. The results of TRAP expression showed a significant decreased (p<0,05) on combination of LPS and NiTi wire with robusta coffee bean extract gel. Robusta coffee bean extract gel was able to reduce TRAP expression on periodontitis model rats induced by the combination of LPS P. gingivalis and NiTi wire.